Which quadratic equation is equivalent to (x 2)2 5(x 2) – 6 = 0? (u 2)2 5(u 2) – 6 = 0 where u = (x – 2) u2 4 5u – 6 = 0 where u = (x – 2) u2 5u – 6 = 0 where u = (x 2) u2 u – 6 = 0 where u = (x 2)

Respuesta :

The quadratic equation which equivalent (x + 2)² + 5(x + 2) - 6 = 0 is u² + 5u - 6 = 0 where u = x + 2

What is an equation?

An equation is an expression that shows the relationship between two or more number and variables.

Given the quadratic equation:

(x + 2)² + 5(x + 2) - 6 = 0

Let u be equal to x + 2, the equation gives:

u² + 5u - 6 = 0

The quadratic equation which equivalent (x + 2)² + 5(x + 2) - 6 = 0 is u² + 5u - 6 = 0 where u = x + 2

Find out more on equation at: https://brainly.com/question/2972832

#SPJ4

Answer:

c

Step-by-step explanation: